GENESIS AND MODERN MANIFESTATIONS OF DESTRUCTIVE SUBCULTURES (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This study examines the genesis and modern manifestations of destructive subcultures among academic lyceum students in Uzbekistan. The research identifies three interconnected factor domains—internal psychological (adolescent instability, identity crisis, conformity), external social (socio-economic problems, injustice, labor market uncertainty), and family-educational environment (dysfunctional families, insufficient parental control, social alienation)—that collectively increase youth vulnerability to destructive influences. Special emphasis is placed on digital technologies as primary dissemination mechanisms, particularly social media platforms (Telegram, Instagram, TikTok) operating through algorithmic “echo chamber” effects that amplify exposure to violent and antisocial content. Drawing on identity development theory (Marcia) and sociology of deviance (Erikson), the dissertation proposes systematic pedagogical interventions including the “Qadam-baqadam” technology, group and individual counseling, and meaningful leisure organization to foster constructive subcultural redirection and youth protection.